A principled evaluation of the effectiveness of selected aspects of the OECD's BEPS proposals to prevent "tax treaty abuse" - Davids, Tharwah (Department of Finance and Tax, 2016)
The BEPS Action 6 Report identified "tax treaty abuse", and in particular "treaty shopping", as one of the most important sources of BEPS. As such, the objective and purpose of the Action 6 Report is intended to address "the granting of tax treaty benefits in inappropriate circumstances" to prevent the perceived "tax treaty abuse". This has been a primary focus for the BEPS project. This paper evaluates the effectiveness of selected aspects of the BEPS proposals against this purpose and objectives of the OECD BEPS project. To evaluate the effectiveness of these proposals, this paper examines the development of basic principles to understand what is meant by the term "tax treaty abuse". An overview of these developments proposes to provide clarity and ensure that the broader context is conceptualised for the purposes for this paper.